2015
DOI: 10.1016/j.shaw.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microbial Load in Oropharyngeal Mucosa from Tannery Workers

Abstract: BackgroundAnimal skin provides an ideal medium for the propagation of microorganisms and it is used like raw material in the tannery and footware industry. The aim of this study was to evaluate and identify the microbial load in oropharyngeal mucosa of tannery employees.MethodsThe health risk was estimated based on the identification of microorganisms found in the oropharyngeal mucosa samples. The study was conducted in a tanners group and a control group. Samples were taken from oropharyngeal mucosa and inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Lower levels of IgA could increase the possibility of various nasal or air-borne infections, possibly caused by fungus and other opportunistic pathogens like Candida albicans . We found that about 14% of the tanners had fungal and bacterial infections on body surfaces, which was in agreement with a previous report that found tanners to be prone to fungal and other types of infection 33…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lower levels of IgA could increase the possibility of various nasal or air-borne infections, possibly caused by fungus and other opportunistic pathogens like Candida albicans . We found that about 14% of the tanners had fungal and bacterial infections on body surfaces, which was in agreement with a previous report that found tanners to be prone to fungal and other types of infection 33…”
Section: Discussionsupporting
confidence: 93%
“…We found that about 14% of the tanners had fungal and bacterial infections on body surfaces, which was in agreement with a previous report that found tanners to be prone to fungal and other types of infection. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that E . asburiae strains have been isolated from water, soil, food, and human sources, that is, blood culture, wounds, and exudates as well as from respiratory sources (Brenner, McWhorter, Kai, Steigerwalt, & Farmer, ; Castellanos‐Arévalo, Castellanos‐Arévalo, Camarena‐Pozos, Colli‐Mull, & Maldonado‐Vega, ; Khalifa, Alsyeeh, Almalki, & Saleh, ; Shin et al., ). Although its exact clinical value is yet to be discovered and very little is known about its pathogenicity and virulence, these findings suggested the clinical significance of E. asburiae .…”
Section: Introductionmentioning
confidence: 99%
“…5,13,35 The severity varies on individual physical characteristics including allergen sensitivity, immune capacity and exposure duration to the contaminants. 36 Occupational factors may play a synergistic role with pre-existing predisposition to allergy. 37 In present study the major chemicals reported to be handled by workers in pre-tanning and tanning process aredemonstratedas potential irritant and sensitizer.…”
Section: Discussionmentioning
confidence: 99%